Whole-Genome DNA Methylation Sequencing Reveals Epigenetic Changes in Myelodysplastic Syndromes - Zhou, Jing-dong; Xu, Zi-jun; Jin, Ye; Zhang, Xin-long; Gu, Yu; Ma, Ji-chun; Wen, Xiang-mei; Lin, Jiang; Zhang, Ting-juan; Qian, Jun (Frontiers in Oncology, 2022)
Epigenetic dysregulation of cancer-associated genes have been identified contributing to the pathogenesis of myelodysplastic syndromes (MDS). However, few studies have elucidated the whole-genome DNA methylation in the initiation pathogenesis of MDS. Reduced representation bisulfite sequencing was performed in five de novo MDS patients and four controls to investigate epigenetic alterations in MDS pathogenesis. The mean global methylation in five MDS patients showed no significant difference as compared with four controls. In depth, a total of 1459 differentially methylated fragments including 759 hypermethylated and 700 hypomethylated fragments were identified between MDS patients and controls. Targeted bisulfite sequencing further identified that hypermethylation of DLEU7, FOXR1, LEP and PANX2 were frequent events in an additional cohort of MDS patients. Subsequently, LEP hypermethylation was confirmed by real-time quantitative methylation-specific PCR in an expanded cohort of larger MDS patients. In clinics, LEP hypermethylation tended to be associated with lower bone marrow blasts and significantly correlated with U2AF1 mutation. Survival analysis indicated that LEP hypermethylation was associated with markedly longer survival time, but was not an independent prognostic biomarker in MDS patients. Functional studies revealed pro-proliferative and anti-apoptotic effects of Leptin in MDS cell line SKM-1, and significantly associated with cell growth and death as well as Toll-like receptor and NF-kappa B signaling pathway. Collectively, our findings demonstrated that whole-genome DNA methylation analysis identified novel epigenetic alterations such as DLEU7, FOXR1, LEP, and PANX2 methylations as frequent events in MDS. Moreover, LEP might play a role in MDS pathogenesis, and LEP hypermethylation was associated longer survival but not as an independent prognostic biomarker in MDS.